Violent Firearm Injury and Homelessness: Examining the Experiences of Black Men Participating in Hospital-Based Violence Intervention Programs - William Wical; Lea Marineau; Nazsa Baker; Bethany Strong; Nakita Lovelady; Joseph B. Richardson (American Journal of Men's Health)
Both experiencing homelessness and having survived a violent firearm injury are well-known risk factors for being a victim of violence. Despite there being significant racial disparities in these factors, there is no qualitative research examining the experiences of Black men who survive a gunshot wound and were homeless after their injury. Drawing on over a year of ethnographic research at the two busiest hospital-based violence intervention programs in the state of Maryland, this research centers the experiences of violently injured homeless Black men to understand how to best support their health, healing, and social goals. Emergent themes from the research included the significant need for housing after injury, challenges with healing while homeless, and difficult experiences with housing institutions. The findings suggest that additional supportive care services for Black men who survive gunshot wounds are needed to increase access to safe and stable housing.